Nicotinamide Mononucleotide Administration Prevents Doxorubicin-Induced Cardiotoxicity and Loss in Physical Activity in Mice - Margier, Marielle; Kuehnemann, Chisaka; Hulo, Nicolas; Morales, Jazmin; Ashok Kumaar, Prasanna Vadhana; Cros, Cecile; Cannelle, Helene; Charmetant, Julie; Verdin, Eric; Canault, Matthias; Grozio, Alessia (Cells (Basel, Switzerland), 2022)
Doxorubicin (Doxo) is a widely used antineoplastic drug with limited clinical application due to its deleterious dose-related side effects. We investigated whether nicotinamide mononucleotide (NMN) could protect against Doxo-induced cardiotoxicity and physical dysfunction in vivo. To assess the short- and long-term toxicity, two Doxo regimens were tested, acute and chronic. In the acute study, C57BL6/J (B6) mice were injected intraperitoneally (i.p.) once with Doxo (20 mg/kg) and NMN (180 mg/kg/day, i.p.) was administered daily for five days before and after the Doxo injection. In the chronic study, B6 mice received a cumulative dose of 20 mg/kg Doxo administered in fractionated doses for five days. NMN (500 mg/kg/day) was supplied in the mice’s drinking water beginning five days before the first injection of Doxo and continuing for 60 days after. We found that NMN significantly increased tissue levels of NAD+ and its metabolites and improved survival and bodyweight loss in both experimental models. In addition, NMN protected against Doxo-induced cardiotoxicity and loss of physical function in acute and chronic studies, respectively. In the heart, NMN prevented Doxo-induced transcriptomic changes related to mitochondrial function, apoptosis, oxidative stress, inflammation and p53, and promyelocytic leukemia nuclear body pathways. Overall, our results suggest that NMN could prevent Doxo-induced toxicity in heart and skeletal muscle.